Competition during early ontogeny: Effects of native and invasive planktivores on the growth, survival, and habitat use of bluegill. (14th January 2019) - Fletcher, Cameron M.; Collins, Scott F.; Nannini, Michael A.; Wahl, David H.
Abstract: Early life stages of fishes are sensitive to ecological and environmental disturbances and experience very high mortality rates. During early ontogeny, the growth and survival of larval fish often depends on food availability. Because habitat and diet shifts are strongly tied to individual body size, factors that influence the growth rates of individuals (e.g. resource limitation, competition) also affect other aspects of ontogeny including the timing of habitat or diet shifts. In the context of biological invasions, non‐native species can potentially disrupt the interaction of larval fish with their food via competition for shared prey, reducing growth and survival during a vulnerable period of an organism's life history. We hypothesised that invasive planktivores negatively affect native species through the vulnerable larval life stage via competition for zooplankton resources. To test this hypothesis, we conducted a series of experiments to assess and contrast the effects of invasive (bighead carp, Hypophthalmichthys nobilis ) and native (golden shiners, Notemigonus crysoleucas ) planktivores on zooplankton densities, and their effects on the growth, survival, abundance, and habitat use of larval bluegill ( Lepomis macrochirus ). Overall, the effects of the invasive planktivore were consistently greater than the native planktivore in terms of reduced prey densities, reduced bluegill growth rates, and delays to the timing of ontogenetic habitat shifts. Growth rates of bluegill larvae were reduced by 58–87% in the presence of bighead carp and 37% in the presence of golden shiners (relative to controls), but such reductions did not consistently lead to reduced survival (in mesocosm experiment) or relative abundance (in pond experiment). However, we estimated that bighead carp and golden shiners delayed ontogenetic habitat shifts in bluegill by 9–24 and 1–3 days, respectively. Although we did not detect an effect of planktivores on the numbers of larval bluegill, our findings suggest that bighead carp may still affect bluegill ontogeny and freshwater food webs by disrupting the timing of ontogenetic habitat shifts. By affecting the coupling of habitats via organism movements during early ontogeny, bighead carp may indirectly disrupt predator–prey interactions of native taxa.